The Plant Stem A Microscopic Aspect - Schweingruber, Fritz H. (Springer Nature, 2018)
Plant stem construction; Plant cell contents; Plant cell walls; Plant meristems; Anatomy of pteridophyta; Stem evolution; Plant ecology; Wood degradation; Fossilization; Plant morphology